PENGARUH KEBIJAKAN PRAKTIK KERJA LAPANGAN (PKL) TERHADAP KESIAPAN KERJA PESERTA DIDIK - Yogaswara, Sri_Marten; Leni Maryani, Leni Maryani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine the effect of Field Work Practices policies on work readiness for class XI students majoring in accounting at Pasundan 1 Bandung Vocational School in the 2022/2023 academic year. Data collection techniques in this study were interviews, questionnaires, and study documentation and to answer these problems using a survey method with a quantitative approach. The population in this study amounted to 67 students. Based on the results of testing the data and the analysis that has been carried out, the results are obtained from the influence of the Field Work Practice policy on work readiness for students XI majoring in accounting at SMK Pasundan 1 Bandung for the 2022/2023 academic year using a coefficient of determination with an R Square value of 74.5 % reached the strong category. These results indicate that the influence of street vendors' policies on the work readiness variable has a contribution of 74.5%, while 25.5% is a factor or other variable that was not investigated by researchers but has a contribution. Suggestions from researchers as the end of research for schools is to establish street vendors based on tighter coordination and selection related to the placement of street vendors so that they are in line with their area of ​​expertise, namely accounting. For the company, namely contacting the school to obtain information related to the areas of expertise of students to adjust the placement of positions at the street vendors.